2011
DOI: 10.1111/j.1582-4934.2009.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Small leucine-rich proteoglycans in atherosclerotic lesions: novel targets of chronic statin treatment?

Abstract: Small leucine-rich proteoglycans (SLRPs), such as decorin and biglycan, regulate the assembly and turnover of collagenous matrix. The aim of the study was to analyse the effect of chronic rosuvastatin treatment on decorin, biglycan and the collagen matrix in ApoE-deficient mice. Twenty-week-old male ApoE-deficient mice received normal chow or 20 mg rosuvastatin/kg × day for 32 weeks. Subsequently, matrix composition was analysed by histochemistry and immunostaining at the aortic root and in innominate arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Together these two mechanisms may cause decreased stability and increased tension and therefore increased susceptibility of the scar to rupture. The function of bgn during fibroblast phenotype regulation might also be important to consider in response to various pharmacologic treatments that affect bgn expression and deposition such, as angiotensin II receptor type 1 antagonists or statins (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Together these two mechanisms may cause decreased stability and increased tension and therefore increased susceptibility of the scar to rupture. The function of bgn during fibroblast phenotype regulation might also be important to consider in response to various pharmacologic treatments that affect bgn expression and deposition such, as angiotensin II receptor type 1 antagonists or statins (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Statins are effective in lowering LDL cholesterol [210] and also reduced plaque volume when used at high dose [210]. ApoE deficient mice treated with statins also display reduced plaque volume with increased decorin and biglycan expression and a more condensed collagen rich ECM, however perlecan expression was not altered in these mice [211] even though it has a major role in LDL retention and has been shown to modulate HS proteoglycan expression [35]. The renin-angiotensin system (RAS) is a central regulatory system for cardiovascular function and critically connected to atherosclerosis and mediated by angiotensin II.…”
Section: Therapies For Fibrosis That Alter Perlecan Expressionmentioning
confidence: 99%
“…23,24 Furthermore, biglycan content is regulated by statins, angiotensin type 1 receptor antagonists, and likely other drugs that are regularly used to treat patients at high risk of cardiovascular events. 18,25,26 No previous studies have addressed the question whether biglycan circulates in patients with coronary heart disease or in ApoE −/− mice. Interestingly, the current study found that circulating concentrations of biglycan are increased in ApoE −/− mice and in patients with acute coronary syndrome.…”
Section: Grandoch Et Al Deletion Of Biglycan Enhances Atherosclerosismentioning
confidence: 99%
“…The conclusion that the absence of biglycan does not crucially affect lipoprotein retention in atherosclerotic plaques is also supported by the observation that chronic treatment with statins dramatically increases the concentrations of biglycan in atherosclerotic plaques without affecting the retention of lipoproteins in late atherosclerosis. 18 Comparing human atherosclerosis-prone internal carotid arteries with atherosclerosis-resistant internal thoracic arteries found no difference in biglycan content. 42 However, the current findings do not rule out the possibility that biglycan contributes to the subendothelial accumulation of lipoprotein during early intimal thickening in humans because biglycan is expressed at sites of subsequent lipid deposition and macrophage accumulation.…”
Section: /Bgnmentioning
confidence: 99%
See 1 more Smart Citation